PENERAPAN ASAS KEADILAN DALAM PELAKSANAAN SIDANG PEMERIKSAAN DUGAAN PELANGGARAN JABATAN NOTARIS DAN ETIKA PROFESI NOTARIS - NURHAPIFAH ASRI LUBIS (PREMISE LAW JURNAL, 2017)
Notary’s is very important as a notary and very much needed by the society concerning his function as the public official who makes written evidence i.e. authentic deeds. Thus, notary deeds also play an important role. In order to prevent illegitimate deeds, this position has to be supervised. The authority to supervise and investigate a notary principally belongs to the Minister of Law and Human Rights. The hearing which investigates the suspicion of violation to notary’s position and professional ethics conducted by the Notary Supervisors has to implement justice principle, as a form of law enforcement. The justice principles are implemented by the Notary Supervisory Board to realize the justice and legal certainty; the Notary Supervisory Board in this regard perform in accordance with the prevailing laws and regulations. Any actions contrary to the laws and regulations will lead to argument and dispute. Keywords: Notary Supervisory Board, Notary’s Position and Code of Ethics